2018
DOI: 10.1097/bpo.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Statistically Significant Results in Pediatric Orthopaedic Randomized Controlled Trials as Quantified by the Fragility Index: A Systematic Review

Abstract: Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
11
47
0
Order By: Relevance
“…Subsequently, any synthesis of related RCTs, although it may present low heterogeneity, carries an inherited risk of extrapolated findings. To nutrition's defence however, lower median FI compared with that of MD interventions has been reported in perioperative, 81 anesthesiology, 82 plastic surgery, 83 and critical-care medicine 84 RCTs, as well as among paediatric orthopedic 85 and appendicitis 86 trials. Nevertheless, the synthesis of these trials for recommendations formulation consists of a common practice in the fields mentioned above, as in the science of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, any synthesis of related RCTs, although it may present low heterogeneity, carries an inherited risk of extrapolated findings. To nutrition's defence however, lower median FI compared with that of MD interventions has been reported in perioperative, 81 anesthesiology, 82 plastic surgery, 83 and critical-care medicine 84 RCTs, as well as among paediatric orthopedic 85 and appendicitis 86 trials. Nevertheless, the synthesis of these trials for recommendations formulation consists of a common practice in the fields mentioned above, as in the science of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The FI for virological cure by day 4 is 1, 2 for day 5, and 4 for day 6 [ Tables 3-5]. [11]. In the field of ophthalmology, the median index is 2 across 156 published trials [10].…”
Section: Resultsmentioning
confidence: 99%
“…Evaniew et al reviewed 40 orthopedic spine surgery trials and reported a median FI of 2 [8]. Pediatric orthopedic trials have a median FI of 3, according to a review by Khormaee et al of 17 trials [11]. In the field of ophthalmology, the median index is 2 across 156 published trials [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaniew et al reviewed 40 orthopedic spine surgery trials and reported a median FI of 2(9). Pediatric orthopedic trials have a median FI of 3, as reported in a review of 17 trials by Khormaee et al(12). In the field of ophthalmology, the median index was 2 across 156 published trials(11).…”
mentioning
confidence: 98%